CLINICAL-COMPARATIVE STUDY OF VIRECHAN & PAKSHAGHATARI GUGGULU ON PAKSHAGHAT W.R.S. TO HEMPIPLIGIA. - KUMAR GUPTA, MANOJ; KANUNGO, NEERAJ; SINGH GAUR, DINESH; SHARMA, SHRIKRISHNA; NIGAM, U.S; KUMAR SINGH, VINOD (Innovare Journal of Life Sciences, 2013)
In the present era due to speeder change of the civilization, human habits and life style continuously changing without any consideration of their benefits or harms Adaptation of new diets, movement with fast moving vehicles, maintenance of wrong postures, avoidance or over-indulgence of exercise, suppression of natural urges, anxiety strain etc. of the present life are becoming responsible for increasing incidence of Vatavyadhi like Pakshaghat (Hemiplegia.) These diseases mostly treated by allopathic medicines(high dose of corticosteroids) which are having considerable side effects and could not be used on long term basis. So conclusion is that in these disease, the dose of allopathic medicines and disease gradually progresses and in addition due to the side effects of allopathic medicines, it is better that these diseases should be treated by Ayurvedic medicines. Â